(untitled) (Bangladesh Journal of Medical Science, 2025)
With three degrees of flexibility, the temporomandibular joint (TMJ) is a synovial bi-condylar joint. It has been observed that temporomandibular joint dysfunction (TMD) affects one-third of adults. Compared to men, females are more frequently impacted. While 75–80% of individuals with TMD require medical intervention and it can take up to three years for the full remission of symptoms, nearly 50% of patients with TMD do not require any treatment and the symptoms resolve on their own within a year of starting. TMD’s clinical manifestations include jaw clenching, clicking, and locking as well as occlusion brought on by bad posture. The diagnosis of temporomandibular disorder (DC/TMD) is based on axis I and axis II diagnoses, according to the 2014 diagnostic criteria for TMD. The purpose of this review is to give a general overview of TMD and look at the various treatment options. Numerous conservative treatment approaches, such as intra-articular injections, cognitive behavioural therapy, manual mobilisation, electrotherapy, dry needling, pharmaceutical treatment, physical therapy modalities, self-care strategies, dental treatment strategies, and surgical corrections, have been shown to be successful. BJMS, Volume: 24. Supplementary Issue 2025, Page : 59-62